Surgery for velopharyngeal insufficiency: The outcomes of the University Hospitals Leuven. Issue 12 (December 2015) - Samoy, K.; Hens, G.; Verdonck, A.; Schoenaers, J.; Dormaar, T.; Breuls, M.; Vander Poorten, V.
Abstract: Objectives: We reviewed the outcomes of patients who underwent a velopharyngoplasty and subsequent speech therapy for velopharyngeal insufficiency (VPI) to determine possible prognostic variables. Methods: During the period 2002–2010, 91 patients with VPI underwent a velopharyngoplasty (either the Honig velopharyngoplasty, the modified Honig velopharyngoplasty or the Hynes pharyngoplasty). Of these, 62 had complete data for long-term evaluation of speech outcome and analysis of variables potentially influencing this outcome. Speech outcome was assessed using five criteria that were evaluated pre- and postoperatively: hypernasality, nasal emission, facial grimacing, retro-articulation and glottal stops. The former two variables were transformed into a semi-objective nasality index (NI), the latter three variables were assembled to form a subjective articulation index (AI). Prognostic variables for outcome that were studied included age at velopharyngoplasty, associated 22q11.2 deletion syndrome, intervention type, primary or secondary surgery and pre-intervention speech therapy. Results: Before surgery, based on the NI, 15 patients had mild VPI and 44 patients had moderate to severe VPI. Postoperatively at 12 months, 46 patients had a good speech outcome (normal or mild VPI), 13 patients had moderate VPI and no more severe VPI was observed. The overall success rate of 78% after one year increased to 90% in the long-term (median 27 months) with further speech therapy. Patients without the diagnosis of 22q11.2 deletion syndrome had better speech outcomes than patients with the syndrome. No statistically significant effect of the age at velopharyngoplasty on speech outcome was found. No cases of sleep apnea syndrome were reported. Conclusions: Our protocol of patient tailored surgical interventions and further postoperative speech therapy results in good speech outcomes, with no or only mild remaining VPI for the majority of patients. The correction of VPI is more difficult for the subgroup of patients with 22q11.2 deletion syndrome.